ANALISIS FUNDAMENTAL SAHAM TERHADAP KEBIJAKAN PEMBAYARAN DIVIDEN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2015 - 2018) - Lutfiati Choridah; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT This study aims to determine the effect of Cash Ratio, Current Ratio, Total Asset Turnover, Return on Capital, Earnings Per Share and Debt to Equity Ratio on Dividend Payment Ratios on Manufacturing Companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2018 period, using sampling techniques targeted at companies produced in 2015-2018 and using multiple linear regression analysis. The results showed that the cash ratio, current ratio, total asset turnover, return on equity, earnings per share and debt to equity ratio has no effect on the Dividend Payment Ratio. Partial Test (t test) is used to find out whether it has an effect or not. The test criteria state if the probability is <level of significance (α), while the test criteria state that the cash ratio does not affect the dividend payout ratio, the current ratio does not affect the dividend payout ratio, the total balance sheet has no effect on the payment ratio, studies that equity returns do not affect dividend payout ratios, write-off per share does not affect dividend payout ratios, debt to equity ratios do not affect dividend payout ratios. This research is expected to contribute to investors in making investment decisions. Keywords        : Cash Ratio, Current Ratio,Total Assets Turnover, Return On Equity, earning Per Share, Debt to Equity Ratio, Dividend Payout Ratio